Modelling of Different Types of SOA Characteristics - Ong Y.S.; Yusoff N.M.; Kharraz O.M.; Sulaiman A.H.; Abdullah F. (Institute of Electrical and Electronics Engineers Inc., 2023)
Fiber amplifiers; Fiber lasers; MATLAB; Models; Optical switches; Semiconductor optical amplifiers; Amplified spontaneous emission noise; Gain medium; Linear and nonlinear types; Multi wavelength fiber laser; Optical power; OPTISYSTEM; Steady-state modeling; Travelling waves; Nonlinear optics